2020
DOI: 10.1002/solr.202000358
|View full text |Cite
|
Sign up to set email alerts
|

Examining the Interfacial Defect Passivation with Chlorinated Organic Salt for Highly Efficient and Stable Perovskite Solar Cells

Abstract: In perovskite solar cells (PSCs), the interfaces between perovskite film and charge transport layers have an enormous influence on the device performance and stability. Recently, it has been proven that the surface defect passivation of perovskite layer is an effective strategy to improve the device efficiency. Herein, an organic ammonium salt benzyltriethylammonium chloride ([BZTAm]Cl) is used as an ultra‐thin modification layer in perovskite films in MAPbI3 PSCs for passivating the surface defects. The obtai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
23
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 23 publications
(25 citation statements)
references
References 51 publications
2
23
0
Order By: Relevance
“…Particularly, the ideal scenario for mixed dimensionality devices will need to be distinguished from that of the 2D devices. ALA has also been used for tin-based devices, with “n = 9” giving efficiencies up to 9.48% …”
Section: Thin Film Case Studies Using Different Perovskite Layer Arch...mentioning
confidence: 99%
“…Particularly, the ideal scenario for mixed dimensionality devices will need to be distinguished from that of the 2D devices. ALA has also been used for tin-based devices, with “n = 9” giving efficiencies up to 9.48% …”
Section: Thin Film Case Studies Using Different Perovskite Layer Arch...mentioning
confidence: 99%
“…X-ray diffraction (XRD) study has been carried out for observation of the crystallinity of single layer (without GO) and trilayer (with GO) perovskite films, as shown in Figure 2a. The perovskite film without GO exhibits the characteristic XRD peaks at 14.24, 28.60, and 31.96 degrees, which represent the (110), (220), and (310) lattice planes, respectively [34,35]. More interestingly, no PbI 2 residual peak has been found in both (with and without GO) perovskite films.…”
Section: Resultsmentioning
confidence: 95%
“…This will result in the further decrease in the carrier recombination at the interfaces, improving the device performance. Obviously, the improved morphology, such as the reduction in the pinholes and cracks (as discussed in Figure 2) would have contributed to the enhanced photocurrent in the trilayer structure [34,44]. The ratio of photocurrent to dark current (I light /I dark ) has been calculated for all four devices at the light illumination intensity of 0.1 mWcm −2 , and a bias voltage of 5 V. The calculated values of I light /I dark for the devices have been shown in Table S1 of the Supplementary Materials.…”
Section: Resultsmentioning
confidence: 99%
“…The reduction in trap state density for device deposited on SnO 2 ‐TH may result from the improved crystallization of perovskite film due to the presence of pyridine cation and Cl − . [ 20,37 ]…”
Section: Resultsmentioning
confidence: 99%
“…introduced NH 4 Cl into the SnO 2 precursor and showed that ammonium ion and chloride anion at the SnO 2 /perovskite interface can suppress the formation of deep‐level defects. [ 17 ] Additionally, some other organics (e.g., 4‐imidazoleacetic acid hydrochloride, [ 18 ] NH 4 F, [ 12b ] girard's reagent t (GRT), [ 19 ] organic ammonium salt benzyltriethylammonium chloride ([BZTAm]Cl), [ 20 ] etc. ), especially fullerene derivatives (e.g., chlorinated fullerene dimers, [ 21 ] [6,6]‐phenyl‐C61‐butyric acid methyl ester, [ 22 ] etc.…”
Section: Introductionmentioning
confidence: 99%